A global assessment of actors and their roles in climate change adaptation - Petzold, Jan; Hawxwell, Tom; Jantke, Kerstin; Gonçalves Gresse, Eduardo; Mirbach, Charlotta; Ajibade, Idowu; Bhadwal, Suruchi; Bowen, Kathryn; Fischer, A. Paige; Joe, Elphin Tom; Kirchhoff, Christine J.; Mach, Katharine J.; et al. (Nature Portfolio, 2023)
Abstract An assessment of the global progress in climate change adaptation is urgently needed. Despite a rising awareness that adaptation should involve diverse societal actors and a shared sense of responsibility, little is known about the types of actors, such as state and non-state, and their roles in different types of adaptation responses as well as in different regions. Based on a large n -structured analysis of case studies, we show that, although individuals or households are the most prominent actors implementing adaptation, they are the least involved in institutional responses, particularly in the global south. Governments are most often involved in planning and civil society in coordinating responses. Adaptation of individuals or households is documented especially in rural areas, and governments in urban areas. Overall, understanding of institutional, multi-actor and transformational adaptation is still limited. These findings contribute to debates around ‘social contracts’ for adaptation, that is, an agreement on the distribution of roles and responsibilities, and inform future adaptation governance.